Relaxation behavior of laser-peening residual stress under tensile loading investigated by X-ray and neutron diffraction - Koichi AKITA (The Japan Society of Mechanical Engineers, 2014)
Compressive residual stresses induced by peening techniques improve the strength properties of steels, such as fatigue and stress corrosion cracking. However, the compressive residual stress might be reduced owing to thermal and mechanical loading in-service. In this study, the behavior of surface and internal residual stresses of a laser-peened ferritic steel under quasi-static tensile loading was investigated by X-ray and neutron diffraction. The complementary use of these diffraction techniques provided decisive experimental evidence for elucidating the relaxation process. As the applied tensile stress increases, the inside of the sample yields before the surface yielding at the critical applied stress (the applied stress for the onset of relaxation of the surface residual stress). The internal yielding causes the redistribution of residual stress, resulting in the relaxation of the surface compressive residual stress. Therefore, the relaxation of the surface compressive residual stress under tensile loading starts before the surface yielding. The critical applied stress of peened samples subjected to a tensile loading can be estimated from the von Mises yield criterion with the maximum tensile residual stress inside the sample. The FWHM of X-ray diffraction profile of the sample surface was increased by laser-peening, and it was further increased by further plastic deformation after peening.